1936
DOI: 10.1104/pp.11.2.343
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Temperatures and the Cooling of Leaves by Radiation

Abstract: There has been marked disagreement among plant physiologists relative to the effectiveness and importance of transpiration in cooling the leaves of plants. SMITH (12), CLUM (4), CURTIS (5), and others have concluded that the cooling effect is slight and rarely of importance in preventing excess heating, whereas, SHULL (10), EATON and BELDEN (7), ARTHUR and STEWART (1), CLEMENTS (3), and others have concluded that the cooling effect may be great. The latter investigators especially have claimed that the cooling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

1936
1936
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 6 publications
1
27
0
2
Order By: Relevance
“…Differences as large as 80 C were measured under very clear, calm conditions. This observation agrees also with the data of others (6,7,12,29). The observations, table V, that lower sheltered leaves on clear and cloudy days and upper exposed leaves on clear and cloudy nights are cooler than the air agrees with the negative value of (T'-T) predicted in table IV.…”
Section: The Energy Economy Equationsupporting
confidence: 94%
See 1 more Smart Citation
“…Differences as large as 80 C were measured under very clear, calm conditions. This observation agrees also with the data of others (6,7,12,29). The observations, table V, that lower sheltered leaves on clear and cloudy days and upper exposed leaves on clear and cloudy nights are cooler than the air agrees with the negative value of (T'-T) predicted in table IV.…”
Section: The Energy Economy Equationsupporting
confidence: 94%
“…MILLER and SAUNDERS (21) and EATON and BELDEN (10) attempted to observe leaf temperatures by clamping a thermocouple against leaves by means of a cork. CURTIS (7) found that leaf temperatures taken by this method were 0.9 to 3.7°C cooler than the temperature of a couple threaded into the leaf because the cork shaded the leaf. Many workers (6,7,24,32) have measured leaf temperatures by threading a thermocouple into the leaf.…”
Section: Methodsmentioning
confidence: 87%
“…Radiation to and from leaves and fruit, and convective heat transfers, can lead to tissue temperatures significantly different from ambient air temperatures [29,126,129], and cooler leaves often are sites for dew deposition [72]. Dew and other forms of surface wetness invite bacterial and fungal pathogens (Sect.…”
Section: Greenhouse Structures and Climate Control Equipmentmentioning
confidence: 99%
“…If, in the experiments reported here the temperature of Bordeaux-sprayed leaves was lowered from 1 to 20 C., as they state in case of sprayed potato leaflets, a significant change in the vapor pressure gradient between the leaf and the external air would have taken place. CUR.S (6) shows that a 1 to 20 C. reduction in leaf temperature, between a range of 10 and 400 C., is equivalent to raising the external humidity as much as 5 to 14 per cent. Since the rate of transpiration is governed by the steepness of the vapor pressure gradient existing between the intercellular spaces and the external atmosphere, any comparative decrease in vapor pressure within the leaf, other conditions remaining constant, would reduce this gradient and lower the rate of transpiration.…”
Section: Discussionmentioning
confidence: 99%